DEVELOPING PROCEDURE TEXT MATERIALS FOR THE ELEVENTH GRADE STUDENTS OF COMPUTER AND NETWORK ENGINEERING - Citra Indah Maharani Laoli; Yeni Erlita (Universitas Negeri Medan, 2017)
The objective of this study is to develop suitable procedure text materials for reading skill, for computer and network engineering students. It was found that procedure text materials provided in the students’ textbook were not suitable to the needs and interests of computer and network engineering students. This research was conducted based on educational research and development (R&D) through five steps, namely: gathering data, analyzing data, developing procedure text materials, validating procedure text materials, and revising procedure text materials. The subject of this study was XI-3 TKJ students at SMK Harapan Stabat and the instruments used to collect the data were observation list, questionnaire, and interview. Based on the needs analysis conducted there were 6 procedure texts related to computer and network engineering developed. These texts were accompanied by vocabularies and 12 varied exercises. These developed procedure text materials had been validated by two experts and the average score gotten is 4.18. It is categorized “Good” since the mean is within the interval 3.40 < ≤ 4.19. It means that the developed procedure text materials for reading skill are suitable for the eleventh grade students of computer and network engineering.